Impactos socioambientais causados pelas cheias excepcionais do Rio Negro em Manaus - AM ocorridas entre 1950 a 2015 - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
The study of extreme events, specially the exceptional floods, has become increasingly necessary in Manaus for planning purposes both in the form of action to coping as for prevention for avoiding losses of materials and lives. The objective of the research was to analyze the environmental impacts caused by exceptional floods of the Rio Negro in Manaus, in the period from 1950 to 2015. Field and office researches were held and after data collection, it moved to the next phase: analysis and systematization of data obtained in the collection phase. With the obtained results, we conducted an analytical discussion pointing out problems and suggesting actions as alternative solutions. The recurrence of exceptional floods is increasing and, depending on their behavior in regard to intensity and duration, the results are great losses in all aspects: in the circulation of goods and people, in education, trade and services, housing and mainly in health, in which we regret negative data deaths. The results show that the Government needs to innovate, create alternatives that enable the planning and execution of an urban redevelopment, providing opportunities for the least favored to a housing policy, in which the priority is to act efficiently and effectively in the removal of families occupying irregularly the areas of the river basins (watersheds) of Educandos and São Raimundo subjected to flooding. Intensify, in all segments, the transdisciplinarity of Environmental Education as well as the recovery and preservation of river channels and areas of permanent preservation. It is necessary to encourage and invest in studies that show definitive solutions to such a serious problem and it must be a number one priority for the governance of the city of Manaus. Keywords: Exceptional Flooding, Impacts, Watershed, River Channels.
Keywords: Cheia Excepcional; Impactos; Bacia Hidrográfica; Canais Fluviais; CIÊNCIAS HUMANAS: GEOGRAFIA: GEOGRAFIA REGIONAL